Accessibility: a case of "us and them"? - Matthew T. Atkinson; Colin Machin (2007)
Why bother researching into enabling better access for disabled people to computer systems, especially the increasingly important area of virtual worlds? What benefits could this research possibly give to wider society? This paper presents an overview of our past and ongoing research in the areas of accessibility and usability, in an effort to explain how such work can benefit us all. It then discusses game and virtual world accessibility in more depth and brings the other strands of our work into this context.